Durable Displacement and the Protracted Search for Solutions: Promising Programs and Strategies. (March 2023) - Ferris, Elizabeth; Kerwin, Donald
In March 2022, the Center for Migration Studies of New York (CMS) hreleased a request for papers (RFP) for a special issue of its Journal on Migration and Human Security (JMHS), devoted to identifying solutions to situations of protracted displacement. The co-editors selected 10 papers for this special issue by authors from a dozen countries, including two refugees. The papers cover several large populations in protracted displacement, as well as other less-publicized groups. The former include: Rohingya refugees in Cox's Bazar, Bangladesh; Internally displaced persons (IDPs) living on the outskirts of Baku, Azerbaijan; Afghans in Pakistan since the 1970s; Syrians in Turkey since 2011; Syrian, Iraqi, Yemeni, Sudanese, Somali, and Iranian refugees in Turkey, Jordan, and Lebanon; IDPs and Venezuelan migrants in Colombia; Somali refugees in Ethiopia and Kenya; Central Americans seeking protection in Mexico and the United States; and IDPs in Northern Mexico who have been displaced and stranded due to violence, deportation, and US and Mexican asylum policies. This paper introduces and integrates the themes and recommendations from this special issue. Section 1 provides a short overview of the scope, growth, and consequences of protracted displacement. Section 2 situates this phenomenon in a legal context and examines traditional and complementary solutions to displacement. Section 3 outlines topline findings, recommendations, and cross-cutting themes from the special issue. Section 4 offers conclusions and final reflections.